PENERAPAN VALUE ENGINEERING PADA BANGUNAN TEBING SUNGAI BATANG ASAI DI KABUPATEN SAROLANGUN (APLICATION OF VALUE ENGINEERING ON RIVER BANK BATANG ASAI) - Laksono D Nugroho (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2012)
Value engineering Analysis performed on construction Batang Asai river Bank revetment at Sarolangun District is considered extravagant dimensions. This study aims to obtain alternative structures more efficient and effective and know the amount saving that occur after the ValueEngineering.